Effectiveness of Single-Dose Postoperative Antibiotics in Patients Undergoing Ureteroscopy in a Tertiary Care Center - Shah, Amit Kumar; Kharel, Shrijan; Verma, Sumit; Pun, Deepak; Baskota, Bashu Dev (Journal of Nobel Medical College, 2026)
Background: Ureteroscopy is a commonly performed procedure in the management of ureteric calculi; however, postoperative infectious complications are a cause for clinical concern. Antibiotic prophylaxis is routinely used for mitigating such risks. Current guidelines advise a single dose of preoperative antibiotic but many centers continue postoperative antibiotics administration despite a lack of solid evidence. This study was designed to compare the effectiveness of single-dose of preoperative antibiotic prophylaxis versus combination pre and postoperative antibiotics in the prevention of infectious complications after ureteroscopy. Materials and Methods: A comparative study was conducted in the Department of Surgery (Urology Unit), B and C Medical college & Teaching Hospital, Birtamod, Jhapa, Nepal. A total of 112 patients with ureteric calculi were randomly assigned into 2 groups; Group A (n = 54) received a single dose of antibiotic preoperatively; and Group B (n = 58) received pre- and postoperatively. All patients underwent ureteroscopy under spinal anaesthesia. Postoperative infectious results, such as cystitis, pyelonephritis and urosepsis, were assessed for 6 weeks post-operatively. Data were analyzed using IBM SPSS statistics version 27. Results: The two groups were comparable in baseline characteristics. Postoperative cystitis occurred in 5.6% of Group A and 13.8% of Group B (p = 0.206). Pyelonephritis was seen in 1.9% vs. 3.4% (p = 1.000), and urosepsis in 1.9% vs. 0% (p = 0.482), respectively. No statistically significant differences were found between groups. Conclusion: A single preoperative dose of antibiotics is no less effective than combined pre- and postoperative antibiotic prophylaxis in the prevention of infectious complications after ureteroscopy.